Experimental skin wound treatment with copaifera langsdorffii desf kuntze (Leguminosae) extract and oil-resin in horses - Kauer, Débora Perrone [UNESP]; Alonso, Juliana de Moura [UNESP]; Gushiken, Lucas Fernando Sergio [UNESP]; Lemos, Marivane; Padovani, Carlos Roberto [UNESP]; Rodrigues, Celso Antonio [UNESP]; Alves, Ana Liz Garcia [UNESP]; Watanabe, Marcos Jun [UNESP]; Bastos, Jairo Kenupp; Pellizzon, Cláudia Helena [UNESP]; Hussni, Carlos Alberto [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Copaifera langsdorffii is a Brazilian native plant that is used for wound healing or as an anti-inflammatory agent. Non-healing wounds are an important health problem, particularly in horses, because they can cause the animal invalidity or even lead to death. In addition, horses respond to skin wounds with chronic inflammatory response and intense wound granulation, thereby delaying the healing process. By this way, our aim was to evaluate the healing potential of Copaifera langsdorffii hydroalcoholic extract (HE) and oil-resin creams (OR) in horse skin wounds. Four wounds were performed bilaterally in the lumbar region of six horses with a 2 cm punch and treated daily with the respective treatments: saline solution, vehicle, 10% HE creams or 10% OR cream. Daily planimetry analyses were performed to measure the wound area and clinical parameters. In four different experimental periods (3, 7, 14 and 21 d), wound biopsies were removed and used for microscopic analyses. SS wounds presented a significant small area at day 3 and 7, OR wounds presented significant small area in comparison with HE at 14 d, and no significant difference was observed between treatments at 21 d. A better microscopic and clinical healing activity of HE and OR was identified in comparison with the controls. The OR group showed better healing quality, specifically after 7 d of treatment. Therefore, Copaifera langsdorffii formulations demonstrated their wound healing potential in horse skin lesions, exhibiting an improvement of the macro-and microscopic parameters.
Tratamento experimental de feridas cutâneas com extrato e óleo resina de copaifera langsdorffii desf kuntze (Leguminosae) em equinos
Keywords: Copaiba; Healing; Phytotherapy